Self-Refine Enhances CodeGen-2B HELM Scores Over Standard Decoding - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 11 peer-reviewed papers addressing the following research question: What is the quantitative improvement in HELM scores for codegen-2b when applying Self-Refine versus standard decoding strategies. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 5.5/10. This report is a machine-generated literature synthesis and does not constitute or
Machine-generated literature synthesis.